Foundations of athletic training prevention, assessment, and management - Anderson, Marcia K. PhD, LATC; Barnum, Mary G. EdD, ATC, LAT (Philadelphia, PA Wolters Kluwer, 2022)
Comprehensive and evidence-based, Foundations of athletic training, 7th edition, integrates basic medical concepts and related scientific information to help readers develop a strong foundation in athletic training best practices. The text's practical, problem solving approach to the prevention, recognition, assessment, management, and disposition of sports-related injuries and diseases helps students learn to think like practitioners. Fully aligned with the BOC competencies, the 7th edition has been extensively updated, expanded, and reorganized to reflect the changing role of today's athletic trainer and includes a powerful suite of engaging learning tools to help students succeed
Chapter 1. Athletic training -- Chapter 2. Professionalism and patient-centered care -- Chapter 3. Evidence-based health care -- Chapter 4. Health care administration, leadership, and advocacy -- Chapter 5. Workplace safety: aspects of prevention, health, wellness and safety -- Chapter 6. Mitigation of environmental risk factors -- Chapter 7. Behavioral health and wellness -- Chapter 8.Durable medical equipment and protective devices -- Chapter 9. Protective taping and wrapping -- Chapter 10. Tissue healing and wound care -- Chapter 11. Clinical assessment and diagnosis -- Chapter 12. Acute injuries: assessment and disposition -- Chapter 13. Therapeutic modalities and mechanical interventions -- Chapter 14. Therapeutic exercise program -- Chapter 15. Pharmacology, therapeutic medications, and drug testing -- Chapter 16. Leg, ankle-foot complex -- Chapter 17. Knee conditions -- Chapter 18. Pelvic, hip, and thigh conditions -- Chapter 19. Shoulder condition -- Chapter 20. Upper arm, elbow, and forearm conditions -- Chapter 21. Wrist and hand conditions -- Chapter 22. Lumbar spinal conditions -- Chapter 23. Cervical and thoracic spinal conditions -- Chapter 24. Head and facial conditions -- Chapter 25. Throat, thorax, and visceral conditions -- Chapter 26.Cardiovascular disorders -- Chapter 27. Neurological conditions -- Chapter 28. Respiratory tract conditions -- Chapter 29. Gastrointestinal conditions -- Chapter 30. Endocrine conditions -- Chapter 31. Physical disabilities within active populations -- Chapter 32. Common infectious diseases -- Chapter 33. Dermatology
Includes bibliographical references and index
Keywords: Sports injuries; Sports injuries -- Prevention; Sports injuries -- Diagnosis; Sports physical therapy